Capacidade de locomoção de Ololygon Alcatraz (Anura:Hylidae): subsídios para a conservação Ex Situ - Lisboa, Cybele Sabino (2017)
The current global amphibian situation requires the implementation of efficient conservation measures to minimize or stabilize declines and extinctions rates. Ex situ conservation is a complementary strategy to in situ conservation and is mainly used in captive breeding and maintenance of endangered species for possible reintroductions. It is known that certain abilities can be lost after multiple generations in captivity, generating individuals more adapted to the captive environment. Locomotor function is a fundamental trait to survival, therefore, for an ex situ conservation program it is important to know whether the locomotion and metabolic capacities of captive born and wild animals are similar. Thereby, the present study evaluated the locomotor and metabolic capacities of ex situ and in situ populations of Ololygon alcatraz. This species is bromeligenous, endemic to the Ilha dos Alcatrazes (Brazil) and is threatened, categorized as Critically Endangered on the IUCN and Brazilian red lists. The locomotor performance was measured by manual stimulation of the individuals in an arena and the metabolic capacity was estimated by measuring the maximum activity of enzymes responsible for the production of energy for the locomotion activity. Captives born presented greater resistance to exercise when compared to the wild ones, traveling greater distances, jumping more times and spending more time in exercise, besides presenting higher activity of the enzyme citrate synthase. Wild animals had the potential to perform longer jumps and presented greater activity of the enzyme lactate dehydrogenase, which supports this type of exercise. These differences seems to be explained by phenotypic plasticity, arising from the environment in which individuals were created during ontogenetic development. This study evidenced the need to implement some measures to avoid that such differences are fixed in captives born Ololygon alcatraz and do not compromise their survival if they are translocated to the wild, thus subsidizing the species ex situ conservation program.